A systematic review of school‐based alcohol and other drug prevention programs facilitated by computers or the Internet. (8th October 2012) - Champion, Katrina E.; Newton, Nicola C.; Barrett, Emma L.; Teesson, Maree
Abstract Issues The use of alcohol and drugs amongst young people is a serious concern and the need for effective prevention is clear. This paper identifies and describes current school‐based alcohol and other drug prevention programs facilitated by computers or the Internet. Approach The Cochrane Library, PsycINFO and PubMed databases were searched in March 2012. Additional materials were obtained from reference lists of papers. Studies were included if they described an Internet‐ or computer‐based prevention program for alcohol or other drugs delivered in schools. Key Findings Twelve trials of 10 programs were identified. Seven trials evaluated Internet‐based programs and five delivered an intervention via CD‐ROM. The interventions targeted alcohol, cannabis and tobacco. Data to calculate effect size and odds ratios were unavailable for three programs. Of the seven programs with available data, six achieved reductions in alcohol, cannabis or tobacco use at post intervention and/or follow up. Two interventions were associated with decreased intentions to use tobacco, and two significantly increased alcohol and drug‐related knowledge. Conclusion This is the first study to review the efficacy of school‐based drug and alcohol prevention programs delivered online or via computers. Findings indicate that existing computer‐ and Internet‐based prevention programs in schools have the potential to reduce alcohol and other drug use as well as intentions to use substances in the future. These findings, together with the implementation advantages and high fidelity associated with new technology, suggest that programs facilitated by computers and the Internet offer a promising delivery method for school‐based prevention.